Physiological and technical demands of no dribble game drill in young basketball players - Conte, D.; Favero, T. G.; Niederhausen, M.; Capranica, L.; Tessitore, A. (The Journal of Strength and Conditioning Research, 2015)
This study assessed the physiological and technical demands of no dribble game drill (NDGD) in comparison with a regular drill (RD). Twenty-three young basketball players performed RDs and NDGDs in a random order. All basketball rules were followed for RDs, whereas dribbling was not permitted for NDGDs. The independent variable was the drill condition, and the dependent variables were percentage of maximal heart rate (%HRmax), rate of perceived exertion (RPE), Edwards training load (TL), and the following technical actions (TAs): pass (total, correct, wrong, and percent of correct passes), shot (total, scored, missed, and percent of made shots), interception, steal, turnover, and rebound. Wilcoxon signed-rank tests were applied to assess differences between NDGD and RD conditions for each dependent variable, and the level of statistical significance was set at p = 0.05. Results showed higher values for %HRmax (p = 0.007), Edwards TL (p = 0.006), and RPE (p = 0.027) in NDGD compared with RD condition. Technical action analysis revealed higher values in NDGD than RD for total (p = 0.000), correct (p = 0.000), and wrong pass (p = 0.005), and interception (p = 0.001), whereas no significant differences were found for the other TAs. The main finding of this study was that NDGD condition elicited a greater physiological demand and a higher number of passes and interceptions than the RD one. Basketball coaches should consider the NDGD as a viable method to increase the physiological load of their training sessions and to teach passing skills in a game-based situation.